2014
DOI: 10.1667/rr13413.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chromosome Translocation Rate with Low Dose Occupational Radiation Exposures in U.S. Radiologic Technologists

Abstract: Chromosome translocations are a well-recognized biological marker of radiation exposure and cancer risk. However, there is uncertainty about the lowest dose at which excess translocations can be detected, and whether there is temporal decay of induced translocations in radiation-exposed populations. Dosimetric uncertainties can substantially alter the shape of dose-response relationships; although regression-calibration methods have been used in some datasets, these have not been applied in radio-occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…We previously assessed chromosome trans-location frequencies using fluorescent in situ hybridization (FISH) in separate groups of 79 and 150 radiologic technologists and evaluated the relationships between chromosome translocation rates and estimated occupational radiation doses, finding borderline statistical significance ( 39 , 40 ). We reevaluated ( 41 ) the chromosome translocation dose-response relationship in the 229 biodosimetry study participants using the RBM doses reported here. About 95% of the RBM doses in the combined groups ranged from 0.2– 100 mGy.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…We previously assessed chromosome trans-location frequencies using fluorescent in situ hybridization (FISH) in separate groups of 79 and 150 radiologic technologists and evaluated the relationships between chromosome translocation rates and estimated occupational radiation doses, finding borderline statistical significance ( 39 , 40 ). We reevaluated ( 41 ) the chromosome translocation dose-response relationship in the 229 biodosimetry study participants using the RBM doses reported here. About 95% of the RBM doses in the combined groups ranged from 0.2– 100 mGy.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Epidemiological studies have been carried out in several countries for investigation of cancer risk among medical radiation workers, such as radiologists studied in the UK (Doll, 2005) and the U.S (Matanoski et al, 2008), radiological technologists studied in the U.S (Little et al, 2014;Moskowitz et al, 2014) and Japan (Yoshinaga et al, 1999), and radiotherapy staff studied in Denmark (Andersson et al, 1991). Breast cancer is believed to be one of the most readily caused by ionizing radiation (Snijders et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to locate other publications with similar analyses to compare our findings. One possible contribution to the observed higher excess risk for earlier years could be the increased X-ray energies over time due to improvements in filtering and higher energy of the beam, combined with the known greater biological effectiveness of lower energy radiation 36 37. However, the modifications in radiation energy spectrum are modest and unlikely to fully explain our observations.…”
Section: Discussionmentioning
confidence: 99%